Critical factors for unconventional hydrocarbon resources development - Bravo M, Oscar; Hernández, Diego (CT&F - Ciencia, Tecnología y Futuro, 2021)
Countries all over the world struggle to exploit their Unconventional Hydrocarbon Resources (UHR) to secure energy supply, but only a few of them have succeeded. Regulators and decision-makers should understand the critical factors required for companies to attract capital, technology, and good practices to promote innovation and generate the virtuous cycle that translates into sustainable production. This study seeks to identify the most relevant factors for UHR commercial development. We assessed the UHR exploiting state in 60 countries and identified the critical common development factors for the 22 that are most active. The proposed Unconventional Hydrocarbon Development Index (UDI) allows to model, rank, benchmark, and forecast UHR development activity for any given country. We focused on the case of Colombia to illustrate the validity of this Index. Evidence suggests countries where National Oil Companies (NOCs) address the challenge of exploiting UHR on their own, may lack the required expertise, despite having governmental support and capital availability. It is easier for them to emulate resilient North American firms exploiting UHR by partnering with them to effectively incorporate best practices Governments can facilitate the process through UHR support, surface and subsurface risk reduction, a proper tax regime, and ESG practice promotion.